Lady Windermere syndrome: an inappropriate eponym for an increasingly important condition - Kasthoori, J.J.; Liam, C.K.; Wastie, M.L. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
Non-tuberculous mycobacterial infection (NMI) occurs in elderly women with no pre-existing lung disease, and this has been termed the Lady Windermere syndrome. NMIs are increasing in prevalence and an increasing number of pulmonary mycobacterial infections is due to non-tuberculous mycobacteria. The diagnosis is often difficult because the organism is not readily isolated or cultured, and the condition may not be considered by the radiologist. We report NMI in a 64-year-old woman, based on clinical and radiological findings. Although termed the Lady Windermere syndrome, the name does not correspond to the character in Oscar Wilde's play; hence the eponym is not widely used.